In Vitro Assessment of Antioxidant Enzymes, Phenolic Contents and Antioxidant Capacity of the Verdolaga (Portulacaceae) - Yaaser Q. Almulaiky; Musab Aldhahri; Fahad A. Al-abbasi; Sami A. Al-Harbi; Mohamed H. Shiboob (International Journal of Nutrition, 2020)
In this study, the antioxidants and photosynthetic compounds of Verdolaga were examined. Compounds were extracted from distinctive segments of the verdolaga using various solvents such as methanol (40, 60, 80%), ethanol (40, 60, 80%), acetone (40, 60, 80%), and deionized water. The use of 80% methanol led to the highest extracted concentration of phenolic substances and flavonoids. The extracted products (Leaves, Stem strips, and Root strips) were evaluated for their radical scavenging capabilities with DPPH (IC50= 22.26, 20.56, and 32.10), and ABTS (IC50= 2.86, 3.70, and 5.24), reducing power (EC50= 15.70, 16.39, and 21.69), and peroxide scavenging activity (1C50= 1.717, 2.937, and 3.255), respectively. The extracted products were analyzed by a gas chromatography-mass spectrometer. Peroxidase, catalase, and polyphenol oxidase assays were completed for the crude extract of verdolaga’s leave, stem strips, and root strips. As indicated by these tests, extracts of the verdolaga’s roots, stems and leaves using 80% methanol yielded high antioxidant activity. The most elevated concentrations of extracted chlorophyll, lycopene, and carotenoids were from the leaves and the highest concentration of extracted tannin was noted from strips of stems. The highest measures of peroxidase and polyphenol oxidase were identified in root strips and the highest units of catalase was identified in leaves.
Keywords: Verdolaga